2009
DOI: 10.1074/mcp.m900029-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Plasmodium falciparum Extracellular Secretory Antigens at Asexual Blood Stages Reveals a Cohort of Proteins with Possible Roles in Immune Modulation and Signaling

Abstract: The highly co-evolved relationship of parasites and their hosts appears to include modulation of host immune signals, although the molecular mechanisms involved in the host-parasite interplay remain poorly understood. Characterization of these key genes and their cognate proteins related to the host-parasite interplay should lead to a better understanding of this intriguing biological phenomenon. The malaria agent Plasmodium falciparum is predicted to export a cohort of several hundred proteins to remodel the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…Several studies have addressed this problem by identifying proteins secreted from pathogens into culture media1011. However, such studies potentially miss proteins that are only present in the native context.…”
mentioning
confidence: 99%
“…Several studies have addressed this problem by identifying proteins secreted from pathogens into culture media1011. However, such studies potentially miss proteins that are only present in the native context.…”
mentioning
confidence: 99%
“…[36][37][38][39] The results of the reactivity studies on antibodies carried out by Singh et al 16 also showed that many of the selected parasite extracellular/secreted antigens elicit an immune response during natural infection; however, the specificity and efficacy were not reported. The present study covers a panel of 32 asexual blood-stage proteins (Table 1) reported in the proteomic data of Singh et al 16 for evaluating their potential as an antigen/vaccine candidate and their immunogenicity analysis. Out of 32 proteins, 31 were predicted as probable antigens (except no.…”
Section: Resultsmentioning
confidence: 99%
“…The proteome analysis of P. falciparum asexual blood stages reveals a set of 33 proteins with possible roles in immune modulation to potential antigens. 16 Since the accession number of the highly variable malarial adhesion protein (pfEMP 1) was not provided, it is excluded from the present study. The panel of the selected 32 proteins, of which 27 were novel extracellular antigens, was retrieved from the PlasmoDB7.2 database (http:// plasmodb.org/plasmo/) using the sequence retrieval tools associated with the database (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Proteomics of clinical isolates of malarial parasites is undertaken by institutes such as IISc, Bangalore; ICGEB, New Delhi and IIT Powai, Mumbai. These efforts are providing insights into its physiology whereas proteomic analysis of serum from infected individuals gives preliminary information concerning potential biomarkers [26ā€“29]. Several studies have also been conducted on clinical isolates of wild type and drug resistant varieties of Leishmania across different institutes of the country like NCCS, Pune; JNU, New Delhi; CDRI, Lucknow; IOB, Bangalore; AIIMS, New Delhi; NIPER, Mohali; BHU, Varanasi and IICB, Kolkata [30ā€“44].…”
Section: Reviewmentioning
confidence: 99%